Projektas DigitalPreservationEurope: bendradarbiavimo tobulinimas skaitmeninio išsaugojimo srityje - Kuprienė, Jūratė; Prokopčik, Marija (Information & Media, 2007)
Straipsnyje pristatomo Skaitmeninio išsaugojimo Europoje (DPE) projekto tikslas – skatinti Europoje vykdomų nacionalinių skaitmeninimo projektų ir iniciatyvų bendradarbiavimą ir sinergizmą. Medžiagos skaitmeninimo ir jos skaitmeniniu formatu išsaugojimo uždavinys yra pernelyg didelis ir sudėtingas, kad jį galėtų savarankiškai spręsti atskiros institucijos ar net sektoriai. Su sprendimų, kurių reikėtų skaitmeninei informacijai išsaugoti ir nuolatinei prieigai prie jos užtikrinti, paieškos problema susiduria valstybės sektorius, verslo įstaigos ir net privatūs asmenys. Būtini bendri nacionalinio ir tarptautinio masto veiksmai, kuriuos inicijuoja, koordinuoja ir pristato suinteresuotoms organizacijoms ir visuomenei kompetentingų institucijų konsorciumai, asociacijos, tinklai ir kitokios struktūros. Tai leistų tinkamai atspindėti ir tenkinti įvairių partnerių – kultūros, mokslo, švietimo, verslo institucijų poreikius. DPE vykdomas siekiant gerinti šiuo metu vykdomų skaitmeninės medžiagos išsaugojimo darbų koordinavimą, kooperavimąsi ir sklaidą.DigitalPreservationEurope: development of cooperation in the field of digital cooperationJūratė Kuprienė, Marija ProkopčikSummary Article deals with the project DigitalPreservationEurope (DPE) that aims at fostering collaboration and synergies between national projects and initiatives in Europe in the field of digital preservation and curation. The problem of developing solutions required for the preservation of and provision of continued access to digital information is one that is faced by public sector, commercial organizations and private individuals. There is a need to join national and international activities of expert consortiums, associations and networks that initiate necessary activities and approach, coordinate them and present results to all variety of stakeholders. Community-wide coordination will facilitate pooling of the expertise that exists across the academic, research, cultural, public administration and industry sectors in Europe.The authors present objectives and goals of the project, partner organisations, interaction with other projects and initiatives, first results of the project, namely creation and dissemination of DPE research roadmap in order to deliver a vision of digital preservation and curation, development of the DPE community that should cluster different types of partners, both individual and institutions, to create a framework of members. Faculty of Communication (Vilnius University) is responsible for development of a common training framework providing for a wide pool of practical skills and expertise in digital preservation, while allowing meeting local requirements. Creation of training materials and establishing of a data base of qualified trainers will lead to a certificate in Digital Preservation in future. This activity is based on the “Outline of training principles and objectives”. This deliverable presents structured survey of the area of digital preservation, in particular as regards topics of training and education.Digital preservation, curation and permanent Access are notions that convey commitment to warrant longterm access to digital materials. It means a need for long-term investments that will only pay dividends in long run. In this context DPE has to raise public awareness of digital preservation and its value. DPE’s success will help to secure a shared knowledge base of the processes, synergy of activity, systems and techniques needed for the long-term management of digital objects.